Comparing the fertility desire and related factors in mothers with intellectually disabled children and mothers with healthy children - Sepideh Sheidanik; Mitra Savabi-Esfahani; Zohreh Shahverdi-Asadabadi (Wolters Kluwer Medknow Publications, 2022)
Background: The birth of a child with an intellectual disability is a common event. The fertility desire plays an important role in healthy reproductive programs. This study was conducted to compare the fertility desire and related factors in mothers with intellectually disabled and healthy children. Materials and Methods: The present study was a descriptive, cross-sectional study. The sample size consisted of 348 mothers with healthy and intellectually disabled children (174 per group). Sampling was performed at normal (six schools) and special primary schools (twelve schools) in Isfahan, Iran using stratified random sampling method. Attitude, subjective norms, perceived behavior control, and gender preference were assessed using a researcher-made questionnaire and psychological well-being using Ryff questionnaire. Data were analyzed by descriptive statistics, Independent t-test, Mann-Whitney U test, Chi-square test, and Logistic regression using SPSS 24. Results: In this study, 21.84% of mothers with healthy children and 13.79% of mothers with intellectually disabled children were willing to have other children. The fertility desire in mothers with intellectually disabled and healthy children decreased as their numbers of children (CI 95% =0.14-0.42) and age increased (CI 95% =0.80-0.93) by 0.87 and 0.24, respectively. There was statistically significant difference in mean score of psychological well-being between the two groups of mothers with fertility desire (p = 0.017). There was no statistically significant difference in mean score of attitude, subjective norms, perceived behavior control, and gender preference (p > 0.05). Conclusions: Apparently the awareness of fertility desire and related factors in mothers with healthy and intellectually disabled children may be helpful in healthy fertility counseling.